ТЕКСТ ЯК ОСНОВНА ФОРМА КОНТРОЛЮ ЗНАНЬ СТУДЕНТІВ В РАМКАХ КРЕДИТНО-МОДУЛЬНОЇ СИСТЕМИ НАВЧАННЯ (Педагогіка вищої та середньої школи, 2007)
The article deals with some peculiarities in using test-control as the means of mostly objective grading of students’ knowledge.